Improved anorgasmia following add-on lamotrigine treatment - Seyede Maryam Naghibi; Seyed Hamzeh Hosseini (Shiraz University of Medical Sciences, 2023)
Sexual dysfunction is common after using antiepileptic drugs, and anorgasmia can occur as a treatment-emergent adverse event. The positive effect of lamotrigine on improving anorgasmia in epilepsy patients has been reported in a few studies. Anorgasmia is a common manifestation in epileptic patients. Anorgasmia or ejaculation without achieving orgasm is permanent or recurrent, happening despite adequate stimulation. The current paper presented a 31-year-old male with epilepsy since early childhood who received carbamazepine and phenobarbital. He experienced anorgasmia, and by switching to valproate sodium, the seizures and anorgasmia were somewhat improved. However, both problems were completely resolved after receiving lamotrigine. An 18-month follow-up did not reveal any particular issue. Lamotrigine can be recommended alongside other antiepileptic drugs in patients who have cure-induced anorgasmia. Considering the improvement of anorgasmia and reduced number of seizures, long-term follow-up is recommended.